Metacognitive Writing Strategies Model Used by ESL Writers in the Writing Process: A Study Across Gender - Aripin, Norhartini; Rahmat, Noor Hanim (International Journal of Asian Social Science, 2020)
Writing for English as a second language (ESL) is one of the challenging production skills. Writing skill requires learners to be competent in the use of vocabulary, syntax, grammar, sentence structure, strategies and lexical. In other words, ESL writers should possess adequate language proficiency in order to produce a meaningful text. In the writing process, ESL writers should be guided by writing strategies. Writing strategies are used as a writing regulator that guides the writers to compose productively. Metacognitive writing strategies is one of the writing strategies that involved three main components which are planning, monitoring and evaluating. Hence, this study was conducted to explore metacognitive writing strategies besides constructing a model used by ESL writers in the writing process. Two students from one public university in Johor, Malaysia are grouped according to their gender. This qualitative study used Think-aloud protocol (TAP) as the main method in collecting data. From the findings, it was found that both male and female ESL writers used a variety of metacognitive writing strategies in their writing process, and the female writer used more strategies compared to the male writer. Results of this study have given a great impact on teaching and learning of ESL academic writing.